Hurry up! The role of supervisors' time urgency and self-perceived status for autocratic leadership and subordinates' well-being - Roman Briker; Frank Walter; Michael S. Cole (Personnel Psychology, 2021)
This study examines the connections among supervisors' time urgency, their leadership behavior, and subordinate outcomes. Integrating cognitive perspectives on time urgency with contemporary thinking on the psychological experience of status, we reason that supervisors' time-urgent personality relates positively with their autocratic leadership behavior, and we cast supervisors' self-perceived status as a moderator of this linkage. Moreover, we enrich this leader-centric perspective with a complementary, more follower-centric view, recognizing that the consequences of supervisors' time urgency likely extend beyond their own behavior to indirectly affect their subordinates' well-being at work. We tested our hypotheses using a field sample of 60 supervisors and 277 of their subordinates. Results indicate that (a) supervisors with higher time urgency are more likely to exhibit autocratic leadership behavior when they also perceive themselves as having relatively high status among subordinates, but not when perceiving lower status, and (b) supervisors' time urgency exhibits a conditional indirect effect (via autocratic leadership) on subordinates' work stress and time pressure experiences. Hence, this study illustrates an important boundary condition for the consequences of supervisors' time urgency, and it demonstrates that this personality characteristic not only shapes supervisors' leadership behavior but also affects the subordinates they are charged with leading.
Keywords: 650; authoritarian leadership; autocratic leadership; status; time pressure; time urgency